The impact of serum testosterone level to reflect age-related multi-organ functions - Tomoya Shirakawa; Julius Fink; Zen-u Hotta; Yosuke Shimada; Yan Lu; Junhua Du; Kazuhito Matsushita; Satoshi Hori; Hisamitsu Ide; Shigeo Horie (Endocrine Journal)
The aim of this study is to examine the correlation between aging, serum total testosterone and biomarkers of multiple organ functions in men. The participants consisted of 12,547 outpatients, whose serum testosterone level was measured. A multiple regression analysis was conducted to determine whether biomarkers including hemoglobin (Hb), hematocrit (Hct), luteinizing hormone (LH), follicle stimulating hormone (FSH), alkaline phosphatase (ALP), albumin (ALB), creatinine (Cre), aspartate aminotransferase (AST), alanine aminotransferase (ALT), glucose (Glu), C-reactive protein (CRP), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C) values were associated with serum total testosterone concentration. Significant correlations (p < 0.05) were found between total testosterone and Hb, Hct, LH, FSH, ALP, ALB, TG, HDL-C, AST, ALT, Glu, and CRP. In addition, significant correlations (p < 0.05) were found between Hb, Hct, LH, FSH, ALP, ALB, TG and HDL-C associated with [age × testosterone]. This large-scale study provided new insights into correlations between serum testosterone and biomarkers associated with age-related diseases, suggesting that testosterone is especially important for maintaining homeostasis in aging males. Thus, hypogonadism in elderly patients may be associated with multiple organ dysfunctions.